Equine cutaneous habronematidosis - Navolar, Felipe Martins Negreiros; Kioquetta, Julio Adriano; Ribeiro, Marcela dos Santos; Dearo, Antônio Cezar de Oliveira; Faccin, Tatiane Cargnin (Brazilian Journal of Veterinary Pathology, 2022)
A 4-year-old Quarter Horse stallion was unsuccessfully treated for a circumscribed and ulcerated lesion of unknownduration located lateral to the prepuce (Fig. 1).